Adsorption and charge transfer of lithium at electrified graphene/electrolyte interface. (1st January 2018) - Sun, Sheng; Chen, Liuyan; Sun, Hongliang; Zhang, Tong-Yi
Abstract: Energy profiles and charge transfer in Li adsorption/desorption on/from various charged single layer graphene electrodes in various electrolytes are investigated by hybrid first-principles/continuum calculations. The critical values of excess charge density of graphene and Li, at and above the critical value Li adsorption switches to Li desorption, are −0.87 | e |, 0 | e |, and 1.5 | e | per formula unit for pristine graphene (with formula unit Li1 C32 ) in water, monovacancy graphene (MVSLG, Li1 C31 ) in water and in CCl4, respectively. When moving from far away towards the MVSLG in water and CCl4 during adsorption, Li + ion is gradually reduced to Li atom by charge transfer.